Feasibility and acceptability of undertaking postmortem studies for tuberculosis medical research in a low income country - Ahimbisibwe, Gift; Nakibuule, Marjorie; Martin Ssejoba, Marvin; Oyamo, David; Mulwana, Rose; Nabulime, Josephine; Babirye, Febronius; Kizito, Musana Abdusalaamu; Lekuya, Hervé Monka; Adakun, Akello Suzan; Nalumansi, Daisy; Muryasingura, Stella; et al. (Frontiers in Immunology, 2023)
If we are to break new ground in difficult to treat or difficult to vaccinate diseases (such as HIV, malaria or tuberculosis), we must have a better understanding of the immune system at the site of infection in humans. For tuberculosis (TB), the initial site of infection is the lungs, but obtaining lung tissues from subjects suffering from TB has been limited to bronchoalveolar lavage (BAL) or sputum sampling, or surgical resection of diseased lung tissue. We examined the feasibility of undertaking a postmortem study for human tuberculosis research at Mulago National Referral Hospital in Kampala, Uganda.Postmortem studies give us an opportunity to compare TB-involved and -uninvolved sites, for both diseased and non-diseased individuals. We report good acceptability of the next-ofkin to consent for their relative's tissue to be used for medical research; that postmortem and tissue processing can be undertaken within 8 hours following death; and that immune cells remain viable and functional up to 14 hours after death. Postmortem procedures remain a valuable and essential tool both to establish cause of death, and to advance our medical and scientific understanding of infectious diseases.